Developmental origins and evolution of jaws: new interpretation of "maxillary" and "mandibular" - Cerny, Robert; Lwigale, Peter; Ericsson, Rolf; Meulemans, Daniel; Epperlein, Hans-Henning; Bronner-Fraser, Marianne (Developmental biology, 2004)
Cartilage of the vertebrate jaw is derived from cranial neural crest cells that migrate to the first pharyngeal arch and form a dorsal "maxillary" and a ventral "mandibular" condensation. It has been assumed that the former gives rise to palatoquadrate and the latter to Meckel's (mandibular) cartilage. In anamniotes, these condensations were thought to form the framework for the bones of the adult jaw and, in amniotes, appear to prefigure the maxillary and mandibular facial prominences. Here, we directly test the contributions of these neural crest condensations in axolotl and chick embryos, as representatives of anamniote and amniote vertebrate groups, using molecular and morphological markers in combination with vital dye labeling of late-migrating cranial neural crest cells. Surprisingly, we find that both palatoquadrate and Meckel's cartilage derive solely from the ventral "mandibular" condensation. In contrast, the dorsal "maxillary" condensation contributes to trabecular cartilage of the neurocranium and forms part of the frontonasal process but does not contribute to jaw joints as previously assumed. These studies reveal the morphogenetic processes by which cranial neural crest cells within the first arch build the primordia for jaw cartilages and anterior cranium.
Keywords: Maxilla; Mandible; embryo nesavčí; Coloring Agents; Non-NASA Center; Embryo, Nonmammalian; zelené fluorescenční proteiny; In Situ Hybridization; hybridizace in situ; Cartilage; fluorescein-5-isothiokyanát; Ambystoma; Biological Evolution; Models, Biological; Green Fluorescent Proteins; Neural Crest; zvířata; barvení a značení; kuřecí embryo; Chick Embryo; Morphogenesis; NASA Discipline Evolutionary Biology; morfogeneze; rozvržení tělního plánu; biologická evoluce; Body Patterning; barvicí látky; biologické modely; Fluorescein-5-isothiocyanate; mandibula; Animals; Staining and Labeling; chrupavka; maxila; crista neuralis